RELIGION, POLITICAL POSITION, AND NATION ON SOCIAL MEDIA: REVISITING THE DIALECTICS AND DISCOURSES ON THE JAKARTA LEADERSHIP AMONG SOCIAL MEDIA (INSTAGRAM) USERS - Ahmad Hakam (Bethel Press, 2024)
This study aims to examine the religious expressions of young Instagram users in Jakarta and its surroundings related to the governor candidates ahead of the 2017 Jakarta Gubernatorial Election, the dialectic of religious views that occur, the reasons behind these religious views. The data in this study were obtained by observation, documentation, and interviews. Data collection and analysis were carried out using qualitative methods. The analysis and interpretation are arranged in a theoretical framework which is reviewed and sourced from several literatures related to the research focus. The results of this study indicate that public expressions on the Instagram official accounts of the 2017 Jakarta governor candidates often discuss religious issues and there are pro and contra dialectics between Islamic and non-Islamic (Christian) leaders, along with their arguments. Religious passion is obviously seen and there is a strong tendency in the public expression of Instagram comments by linking religious aspects to the figure who will lead Jakarta. There are three interrelated themes that become the main argument in dialectics and the opposition whether or not a non-Muslim governor is allowed to become a leader, namely theological, fiqh, and national interest. These views may have been influenced by religious education obtained formally or informally, religious authorities such as ustadz or ulama whose opinions are considered correct, and available online or printed religious information.